Analysis of the Impact of Digital Technology on MSME Business Growth in Bandung City: Case Study on the Use of E-commerce, Digital Marketing, and Online Management System - Putra, Wira Pramana; Hayati, Feb Amni; Andriani, Jeni; Putra, Irsan Herlandi (Westscience Press, 2023)
This study looks into how digital technology has affected the expansion of MSMEs (micro, small, and medium-sized enterprises) in Bandung City. It focuses on online management systems, digital marketing tactics, and e-commerce. A thorough study of 150 MSMEs across a range of industries yielded rich information about their demographic makeup and level of digital technology usage. Regression analysis and structural equation modeling (SEM) were used to evaluate the associations between factors related to digital technology and metrics related to business growth. Because of the measurement model's strong validity and reliability, further studies could be conducted with confidence. Actionable insights for businesses and policymakers were provided by the results, which showed strong positive connections between E-commerce adoption, Digital Marketing, and business success. The significance of E-commerce, Digital Marketing, and Product Innovation in propelling MSME growth was shown by the regression analysis. The results give useful implications for MSMEs in Bandung City and add to the current conversation on digital transformation.